A study of teaching listening - Dara Yusnida; Asnawi Muslem; Abdul Manan (Universitas Syiah Kuala, 2017)
The objectives of this study were to investigate the process of teaching- learning listening at the English Language Education Department of UIN Ar-Raniry in terms of (a) preparation, (b) teaching materials and media used, (c) teaching method/technique/strategy, (d) and evaluation. The subjects of this study were two lecturers who taught listening II classes. The data wase collected through observations, interviews and documentation. The collected data was analyzed and interpreted through qualitative procedures by using data reduction, data presentation, verification and drawing conclusions. The results showed that the two lecturers organized and prepared the lesson plans well before starting the lessons in terms of preparing the listening lessons. However, they did not do the same preparation. The teaching materials were selected from various sources and taken from authentic resources with appropriate media. The teaching methods and techniques used by the English lecturers were various and in accordance with theories for the teaching of listening. In addition, only one lecturer used a scoring guide to evaluate the listening assignments. Meanwhile, the other one used percentage scoring to evaluate the listening tests. Moreover, both lecturers conducted formative and summative assessments when teaching listening.